2018
DOI: 10.1016/j.actbio.2018.05.039
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid injectable hydrogel from hyperbranched PEG macromer as a stem cell delivery and retention platform for diabetic wound healing

Abstract: Diabetic wounds, which are a severe type of diabetes, have become one of the most serious clinical problems. There is a great promise in the delivery of adipose stem cells into wound sites using injectable hydrogels that can improve diabetic wound healing. Due to the biocompatibility of poly(ethylene glycol) diacrylate (PEGDA), we developed an in situ RAFT polymerization approach using anti-alcoholic drug-Disulfiram (DS) as a RAFT agent precursor to achieve hyperbranched PEGDA (HP-PEG). HP-PEG can form an inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(132 citation statements)
references
References 48 publications
2
130
0
Order By: Relevance
“…Hydrogel with low swelling ratio or non‐swelling property will avoid the limitations of weak mechanical toughness caused by swelling and less medical complications, which is a desirable advantage of hydrogels being applied onto wound sites. [ 28 ] First, the morphologies of the hydrogels before and after reaching swelling equilibrium state were observed (Figure 2d). Before swelling test, hydrogel PEGSD2 showed slightly larger pore size than those of hydrogels with gelatin and GTU copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogel with low swelling ratio or non‐swelling property will avoid the limitations of weak mechanical toughness caused by swelling and less medical complications, which is a desirable advantage of hydrogels being applied onto wound sites. [ 28 ] First, the morphologies of the hydrogels before and after reaching swelling equilibrium state were observed (Figure 2d). Before swelling test, hydrogel PEGSD2 showed slightly larger pore size than those of hydrogels with gelatin and GTU copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…At present, many studies have reported that the process of diabetic wound healing was affected by intense and prolonged inflammation; thus, a treatment strategy preventing inflammation shows promising potential for promoting diabetic wound healing [27,28]. A previous study demonstrates that exosomes secreted by macrophage cells influenced inflammatory pathways and contributed to the resolution of inflammation in the recipient cells [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…[426] Another innovative approach is the use of resident MSCs harvested from OA knee arthroscopic flushing fluids recovered from initial clinical knee examinations. This strategy yielded enhanced wound healing of diabetic wounds which have a notoriously poor repair capability similar to OA lesions in articular cartilage.…”
Section: Human Pre-clinical Studies On Mscsmentioning
confidence: 99%